Vegetationsutveckling och mänsklig aktivitet under äldre Stenålder vid Döudden, Arjeplog kommun - Persson, Nina (2004)
The landscape in the interior of Norrland has undergone dramatic changes since the deglaciation as a consequence of faultings, earthquakes and tilting of the landscape westwards. Archaeological investigations along former shorelines by the use of models of isostatic land uplift, have revealed many Mesolitic settlements in northern Sweden. Döudden, in the county of Arjeplog, has been investigated by archaeologists that identified settlements from 5200 BC. The objective of this study was to analyse the history of the vegetation and if the vegetation showed traces of human activity during early Holocene, by pollen analysis. The results indicate that the area had an established vegetation c. 7600 – 8200 BC, consequently the ice must have left the area about 1000 years earlier than has previously been known. The first vegetation consisted of post-glacial vegetation eg. birch (Betula pubeshens), willow (Salix sp.) and sea buckthorn (Hippphaë rhamnoides) for a short period, followed by a total dominance of pine (Pinus sylvestis). Traces of human activity are subtle but the occurrence of charred particles, increased influence of Betula and the presence of light demanding species, it cannot be ruled out that the area was used temporarily by people already c.7500 BC. Landskapet i Norrlands inland har förändrats mycket efter inlandsisens avsmältning med förkastningar, jordbävningar och en tippning av landskapet mot väst som följd. Genom att undersöka tidigare strandlinjer, uträknade via modeller om olikformig landhöjning, har flera boplatser från äldre Stenåldern upptäckts i norra Sverige. Utifrån dessa fynd väcktes intresse att titta närmare på Döudden i Arjeplogs kommun. Där har tidigare arkeologiska utgrävningar visat att platsen varit bebodd i omgångar från 5200 f. Kr. Syftet med denna studie var att ta reda på hur den första vegetationsutvecklingen såg ut och om det eventuellt fanns spår av mänsklig verksamhet under tidig Holocen med hjälp av pollenanalys. Resultaten tyder på att området hade en etablerad vegetation ...